Comparison of Torque Performances on Different Core Material for Switched Reluctance Actuator without Permanent Magnet - Yusri, I.; Ghazaly, M.M.; Ranom, R.; Rahmat, M.F.; Jamaludin, I.W. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This paper presents the comparison of torque profiles of the Switched Reluctance Actuator (SRA) without permanent magnet (PM) using two types of materials which are Low Carbon steel, Grade 1008 and Medium Carbon steel, Grade S45C. Each of the Low Carbon steel and Medium Carbon steel is distinguished by the percentage of carbon contents which is 0.1% and 0.43%, respectively. The designed SRA of both materials was according to the size of NEMA 17 standard stepper motor for small machine applications and simulated through FEM analysis. The maximum generated torque achieved by the SRA with the Low Carbon steel is 122.540mNm and with Medium Carbon steel is 54.107mNm, respectively at 2A input current. It shows that the carbon content influences the magnetic properties of the materials as the generated torque decreases approximately 50% when the carbon content is four (4) times higher. As a conclusion, the Medium Carbon steel, Grade S45C depict better working range as it capable of generating high torque at a small overlapping angle compared to Low Carbon steel, Grade 1008.